Impact of feeding urea ammoniated paddy straw on utilization of nutrients, blood metabolites and cost effectiveness on crossbred lactating cows - SINGH, ANAND; JAISWAL, R S; CHAUHAN, S S; THAKUR, T C; SINGH, VIR; JOSHI, Y P (The Indian Journal of Animal Sciences, 2011)
An experiment on 16 crossbred lactating cows of second and third lactation, producing 6-12 litres of milk!day, was conducted for 91 days to determine the amount of milk production that could be supported by ammonia (urea) treated baled paddy straw (ATBPS) fed ad lib. with small amount of green fodder. The cows were divided into 4 groups on the basis of milk yield and lactation period. The animals in treatment (TI) were fed untreated baled paddy straw (UTBPS) ad lib. along with concentrate mixture, T2 and T3 animals were fed ammonia (urea) treated baled paddy straw (ATBPS) ad lib. and no concentrate was given up to 4 and 5 litres/day milk production, respectively. Treatment (T 4 ) was given farm level diet. It was observed that ammonia (urea) treated paddy straw fed ad lib could support a milk production up to 5 litres ofmilk without any concentrate mixture. There was no significant difference in milk yield and milk composition, except milk urea, which was significantly higher in urea treated diets. Blood constituents like serum protein, glucose and urea were within the normal physiological range. The cost of milk production per litre was reduced by 23.0% and the net income was increased by 33.6% through feeding of urea ammoniated straw diet to lactating cows without any adverse effect on milk yield and milk composition.Â